Fate of arsenic in swine waste from concentrated animal feeding operations - Quazi, Shahida; Punamiya, Pravin; Sarkar, Dibyendu; Makris, Konstantinos C. (My University, 2008)
Swine diets are often supplemented by organoarsenicals, such as 3-nitro-4-hydroxyphenylarsonic acid (roxarsone) to treat animal diseases and promote growth. Recent work reported roxarsone degradation under anaerobic conditions in poultry litter, but no such data exist for swine wastes typically stored in lagoons nearby concentrated animal feeding operations (CAFOs). The objectives of this study were to: (i) characterize a suite of swine wastes collected from 19 randomly selected CAFOs for soluble arsenate [As(V)], arsenite [As(III)], dimethylarsenic acid (DMA), monomethylarsonic acid (MMA), 3-amino-4-hydroxyphenylarsonic acid (3-HPPA), p-arsanilic acid, and roxarsone, and (ii) determine the geochemical fate of roxarsone in storage lagoons nearby CAFOs. Swine waste suspensions were spiked with roxarsone and incubated under dark/light and aerobic/anaerobic conditions to monitor roxarsone degradation kinetics. Arsenic speciation analysis using liquid chromatography and inductively coupled plasma mass spectrometry (LC-ICPMS) illustrated the prevalence of As(V) in swine waste suspensions. Roxarsone underwent degradation to either organoarsenicals (3-HPPA) or As(V) and a number of unidentified metabolites. Roxarsone degradation occurred under anaerobic conditions for suspensions low in solids content, but suspensions higher in solids content facilitated roxarsone degradation under both anaerobic and aerobic conditions. Increased solids content enhanced roxarsone degradation kinetics under aerobic conditions. According to current waste storage and sampling practices, arsenic in swine wastes stored in lagoons has been overlooked as a possible environmental health issue.
Keywords: Arsenic compounds; Chromatographic analysis; Crops; Degradation; Arsenic; High performance liquid chromatography